2018
DOI: 10.14341/osteo9826
|View full text |Cite
|
Sign up to set email alerts
|

Antiresorptive activity of denosumab in the treatment of osteoporosis in patients with rheumatoid arthritis

Abstract: Background: fracture risks assessment and determination of bone mineral density are modern methods, generally accepted and widely used. However, they have limitations and disadvantages for the dynamic evaluation of bone remodeling processes in RA-patients with low BMD. The investigation of bone resorption markers is an important issue. Aims: to compare the antiresorptive activity of denosumab and alendronic acid in patients with rheumatoid arthritis and osteoporosis using β-CTX and osteocalcin (OC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…В нашем исследовании эффективность ДСБ у больных РА подтверждена достоверным снижением маркеров костного обмена через 3 мес после первого введения препарата. Исследование, проведенное в Новосибирске, продемонстрировало также значимое снижение маркеров костного обмена после 3 мес лечения ДСБ больных РА с ОП, в то время как при использовании алендроната и в контрольной группе без антиостеопоротического лечения уровень маркеров существенно не менялся [18].…”
Section: Discussionunclassified
“…В нашем исследовании эффективность ДСБ у больных РА подтверждена достоверным снижением маркеров костного обмена через 3 мес после первого введения препарата. Исследование, проведенное в Новосибирске, продемонстрировало также значимое снижение маркеров костного обмена после 3 мес лечения ДСБ больных РА с ОП, в то время как при использовании алендроната и в контрольной группе без антиостеопоротического лечения уровень маркеров существенно не менялся [18].…”
Section: Discussionunclassified
“…High levels of C-telopeptides were found in women with low BMD. At the same time, OP patients receiving antiresorptive therapy demonstrated a reliable decrease in those markers [ 234 , 235 ]. Different clinical and pre-clinical studies showed enhanced collagen degradation in RA due to the high proteolytic activity of CTX-1 [ 236 ].…”
Section: Aptamers For Protein Biomarkers Of Rheumatic Disordersmentioning
confidence: 99%